Jack Welch And The 4E's of Leadership : How to Put Get's Leadership Formula To Work in Your Organization - Krames, Jeffrey A. (New Dehli Tata McGraw-Hill Publishing, 2005)
Presents the ideas and strategies of Jack Welch.
Include Index and Acknowledgment
Keywords: Competition -- Industrial management -- Leadership